PENGARUH DANA PIHAK KETIGA, NON PERFORMING FINANCING, CAPITAL ADEQUACY RATIO, RETURN ON ASSETS, DAN INFLASI TERHADAP PEMBIAYAAN MURABAHAH BANK UMUM SYARIAH DI INDONESIA PERIODE 2013-2017 - Ibnu Alwiaziz, 15.05.51.0254; Kartika, Andi (Students' Journal of Economic and Management, 2019)
This study aims toexamine the influence of third-party funds, Non Performing Financing, Capital Adequacy Ratio, Return On Assets, and Inflation to Murabahah Financing. The population in this study is syarih banking at Indonesia in 2013-2017. The sampling technique used is genetic sampling technique. Research uses secondary data obtained form annual finance report banking. The data analysis technique used is multipler linear regression analysis. The result show that partially Non Performing Financing dan Return On Assets no effect on murabahah financing. While third-party funds, Capital Adequacy Ratio and inflation partially has a positive influance on murabahah financing. Then simultaneously, third-party funds, Non Performing Financing, Capital Adequacy Ratio, Return On Assets, and Inflation have significantly affects murbahah financing.